Profile of antimicrobial resistance in oncologic pediatric patients - García-Luna, Mauricio; Madrid Gómez-Tagle, José Antonio; O’Brien, Jessica P. (Mexican Journal of Medical Research ICSA, 2014)
The development of resistance to antibiotics is due to the widespread use of a wide variety of antimicrobials, coupled with the ability of bacteria to acquire and spread resistance and the ability of humans to disseminate them. The possible consequences of antimicrobial resistance leads to greater chances of hospitalization, prolongation of hospital stay and increased mortality. Furthermore, treatment of drug resistant bacteria requires the use of more toxic drugs and more expense for the patient and hospitals. The main objective of the present study was to determine the frequency and nature of antimicrobial resistance of microorganisms in oncologic and hematologic patients at a Mexican Pediatric Hospital. A retrospective, observational, and analytical study was realized, where we reviewed the clinical records of 20 cases. Blood cultures were obtained from the Laboratory of our institution from 2010 to 2011. The data obtained were organized and analyzed. We observed that the E. coli and S. aureus were the bacteria most resistant, showing the same percentage between gram-positive and gram-negative bacteria. The cancer diagnosis most common in our study was acute lymphoblastic leukemia. It may be concluded that multidrug-resistant bacteria in these patients are of a nosocomial origin, without a specific group of germ (gram positive vs. gram negative).